1976
DOI: 10.1007/bf00569975
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of alpha-1-antitrypsin phenotypes in two Dutch population groups

Abstract: The alpha1-antitrypsin phenotypes of two Dutch population groups (consisting of 672 and 802 individuals) were determined by the isoelectric focusing technique, which due to its recent development, has been used for the first time in large-scale phenotyping. As in other population studies on the alpha1-antitrypsin phenotype distribution, Pi M is the most frequently occurring allele. The two investigated groups exhibit remarkable differences, both to other studied groups as well as to each other. The most intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Some of the 72 geographically classified studies [13,19,21,23,37,42,59,63] showed remarkable divergent outcomes with respect to the trend of S or Z frequencies for a definite region, according to the figures of the European maps of isogenes (lines of equal gene frequency) [9,11]. These discordant studies were specifically assessed, by comparing S and/or Z 95% CI of its outcomes to S and/or Z calculated 95% CI for hypothetical comparative studies designed with the same sample size of the questioned survey and the maximal or minimal frequencies S and/or Z expected for an specific region, in line with the proposed figures in isogen boundary maps.…”
Section: Methodsmentioning
confidence: 94%
“…Some of the 72 geographically classified studies [13,19,21,23,37,42,59,63] showed remarkable divergent outcomes with respect to the trend of S or Z frequencies for a definite region, according to the figures of the European maps of isogenes (lines of equal gene frequency) [9,11]. These discordant studies were specifically assessed, by comparing S and/or Z 95% CI of its outcomes to S and/or Z calculated 95% CI for hypothetical comparative studies designed with the same sample size of the questioned survey and the maximal or minimal frequencies S and/or Z expected for an specific region, in line with the proposed figures in isogen boundary maps.…”
Section: Methodsmentioning
confidence: 94%
“…Selected studies were distributed as follows: one each from Austria [13], Belgium [14], Latvia [18], Hungary [34], SerbiaMontenegro [62], Sweden [67] and Switzerland [68]; two each from Denmark [15,16], Estonia [17,18] and Lithuania [18,41]; three each from Portugal [53][54][55][56] and the UK [69][70][71]; four each from Finland [19][20][21][22], the Netherlands [42][43][44], Norway [45][46][47] and Spain [62][63][64][65][66]; five each from Russia [57][58][59][60][61] and Germany [29][30][31][32][33]; six from Poland [48][49][50][51]…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] The results of mass screening of the whole population of neonates in Sweden performed over a 2 year period were published in 1976. 21 Of the 200 000 infants screened, 129 had the PI*Z variant, yielding a frequency of 1 in 1550 individuals and a gene frequency of 0.026.…”
Section: Genetic Epidemiology Of Aat Deficiency Europementioning
confidence: 99%